The big push, natural resource booms and growth - Sachs, Jeffrey D; Warner, Andrew M (Journal of development economics, 1999)
A simple application of big-push reasoning suggests that natural resource booms can be important catalysts for development in poorer countries. In this paper we present evidence from seven Latin American countries that natural resource booms are sometimes accompanied by declining per-capita GDP. We present a model with natural resources, increasing returns in the spirit of big push models, and expectations to clarify some of the reasons this may happen.